DEVELOPING STUDENTS' LOGICAL THINKING IN MOTHER TONGUE CLASSES (Western European Journal of Linguistics and Education, 2024)
In this article, instructions and opinions on developing students' logical thinking, correct reasoning, ability to converse on any topic and fluent speaking skills are expressed in mother tongue classes.